A MnCo2O4@NiMoO4 Core‐Shell Composite Supported on Nickel Foam as a Supercapacitor Electrode for Energy Storage. Issue 1 (5th December 2018) - Chen, Tao; Shi, Rui; Zhang, Yuanyuan; Wang, Zhenghua
Abstract: A MnCo2 O4 @NiMoO4 composite was synthesized on nickel foam by a two‐step method. The composite has a core‐shell structure in which MnCo2 O4 nanoneedles are wrapped by NiMoO4 nanoflakes. The MnCo2 O4 @NiMoO4 /Ni foam is applied as a binder‐free electrode for supercapacitors and it achieves a specific capacitance of up to 1718 F g −1 at a current density of 1 A g −1, and 84 % capacitance retention after 6000 charge‐discharge cycles. The capacitance of the MnCo2 O4 @NiMoO4 composite is much higher than MnCo2 O4 nanoneedles and NiMoO4 nanoflakes alone. Moreover, a hybrid supercapacitor is assembled by applying the MnCo2 O4 @NiMoO4 /Ni foam as the positive electrode, activated carbon/Ni foam as the negative electrode. The hybrid supercapacitor reaches an energy density of up to 42.3 W h kg −1 at a power density of 797 W kg −1, a power density of 6256 W kg −1 at an energy density of 17.4 W h kg −1, and 86 % capacitance retention after 2000 charge‐discharge cycles. The results suggest that the rational design of electrode materials with such structure and composition is an effective strategy to improve electrochemical performance. Abstract : Supercapacitors : A Core‐shell structured MnCo2 O4 @NiMoO4 composite has been prepared by a two‐step method and applied as an electrode material for supercapacitors (see figure). In the composite, MnCo2 O4 nanoneedles are wrapped by NiMoO4 nanoflakes, such a structure can provide many active sites for faradaic redox reactions and facilitates the transport of electrolyte. The MnCo2 O4 @NiMoO4 composite exhibits higher specific capacitance than that of the MnCo2 O4 nanoneedles and NiMoO4 nanoflakes alone.